Equivalent Convective Heat Transfer Coefficient for Boundary Conditions in Temperature Prediction of Early-Age Concrete Elements Using FD and PSO - Nguyen-Ngoc, Long; Do, Tu Anh; Hoang, Viet Hai; Hoang, Tuyet Thi; Tran, Tam Duc (KSCE journal of civil engineering, 2023)
Engineering infrastructure includes a large number of concrete structures. The main binder used in concrete is Portland cement, which reacts with water when mixing. During the chemical reaction (cement hydration) heat is released causing non-uniform temperature distribution and subsequent internal stresses that may crack the concrete. Therefore, accurate prediction of concrete temperature evolution in design and control of concrete temperature in construction are crucial tasks for engineers. This paper presents the development of a finite difference (FD) model for predicting thermal behavior of concrete structures during cement hydration. A formwork or insulation layer that covers the outer of the concrete was accounted for in the model. The temperature profiles calculated by the proposed model show close agreement with those measured from a concrete bridge footing and a concrete cube. The Particle Swarm Optimization (PSO) algorithm was adopted to compute an “equivalent convection coefficient” for the convection boundary condition in the simplified model for several common insulation materials. The results show that using the simplified model along with an equivalent convection coefficient can give a significant reduction in the computation time while the accuracy is still maintained. In addition, an equation for estimating an equivalent convection coefficient for a given insulation material was developed for design and practical purposes. The proposed method can be used in the design of concrete structures and control of concrete temperature to prevent early-age thermal cracking thus ensuring the expected durability and service life. From the obtained results, varying equivalent convection values are also recommended to be used for different insulation materials.